UTILIZATION OF DIGITAL MEDIA IN ISLAMIC EDUCATION LEARNING - Patoni, Muhamad; Hasib, Kholili; Rahmatullah, Asep (As-Sulthan Journal of Education, 2026)
The use of digital media in Islamic Religious Education (PAI) has become increasingly significant in response to rapid technological developments, changing student characteristics, and the growing demand for interactive learning. This study aims to explore how digital media is implemented in PAI learning, its effects on students’ learning motivation, and the factors influencing its successful integration. The research employed a qualitative descriptive approach conducted in a secondary education institution. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation analysis of lesson plans and learning materials. Findings show that digital media—such as instructional videos, interactive multimedia, and online learning platforms—significantly enhance student engagement, participation, and motivation. Teachers’ creativity and digital competence, supported by adequate institutional resources and policies, are critical for effective media integration. The study concludes that digital media utilization not only enriches the PAI learning process but also improves learning outcomes, encourages independent and student-centered learning, and strengthens students’ understanding and internalization of Islamic values.